The Elephant in the Room: The Need for Increased Integrative Therapies in Conventional Medical Settings - Missy Hall; Susanne M. Bifano; Leigh Leibel; Linda S. Golding; Shiu-Lin Tsai (MDPI AG, 2018)
Pediatric integrative therapy programs are essential to the treatment and well-being of patients. Identifying an effective integrative therapy model within conventional pediatric medical settings, however, often proves difficult. Our goal in this article is to explore varied solutions to increase access and inclusion of integrative therapies in an effort to promote best practice and holistic care. The main methods applied in this article are vignettes that illustrate how the integrative therapies in a metropolitan academic hospital successfully treat the patient by complementing conventional medicine. This leads to comprehensive care. The central finding of the article proposes viable solutions to increase interdisciplinary collaboration both internally within the institution and externally. Integrative therapists detail how they were able to increase visibility and yield best practice through increased educational initiatives and interdisciplinary collaboration.